Development and Validation of a Reduced DME Mechanism Applicable to Various Combustion Modes in Internal Combustion Engines. (22nd June 2011) - Chin, Gregory T.; Chen, J.-Y.; Rapp, Vi H.; Dibble, R. W.
Abstract : A 28-species reduced chemistry mechanism for Dimethyl Ether (DME) combustion is developed on the basis of a recent detailed mechanism by Zhao et al. (2008). The construction of reduced chemistry was carried out with automatic algorithms incorporating newly developed strategies. The performance of the reduced mechanism is assessed over a wide range of combustion conditions anticipated to occur in future advanced piston internal combustion engines, such as HCCI, SAHCCI, and PCCI. Overall, the reduced chemistry gives results in good agreement with those from the detailed mechanism for all the combustion modes tested. While the detailed mechanism by Zhao et al. (2008) shows reasonable agreement with the shock tube autoignition delay data, the detailed mechanism requires further improvement in order to better predict HCCI combustion under engine conditions.